The Ethical Approach in Assessing the Legitimacy of Constitutional Court Decisions: Urgency and Orientation - Fathorrahman Fathorrahman; Muhammad Juang Rambe; Agung Ali Fahmi (Universitas Negeri Surabaya, 2024)
This study examines the importance of ethics as a formal parameter in assessing the validity of Constitutional Court (MK) decisions in Indonesia. The final and binding nature of MK decisions often raises debates regarding absolute power without adequate control mechanisms, especially in the context of ethical violations. This research explores deontological ethics and procedural justice as the basis for analysis, as well as several controversial MK decisions related to ethical issues. This research is a normative legal study that emphasizes a conceptual and statutory approach. The results show that integrating ethics into the assessment of MK decisions can enhance the legitimacy of constitutional justice and ensure more substantive justice. Therefore, this study recommends reformulating the legal framework to incorporate ethics as a key component in the validity assessment process.